Increasing awareness of diabetes with a health screening program in conjunction with world diabetes day 2023 - Eddy Warman, Nur Aini; Awang, Mohd Hazriq; Mohamad, Aimi Fadilah; Zainordin, Nur Aisyah; Mohamed Shah, Fatimah Zaherah; Abdul Ghani, Rohana (Faculty of Medicine, 2024)
World Diabetes Day is celebrated annually on 14th November and aims to raise awareness about diabetes mellitus. In line with the theme of World Diabetes Day 2023, emphasizing 'Access to Diabetes Care,' the UiTM Endocrine team organized a two-part health screening and education program that extended its reach to the community, emphasizing a commitment to outreach and engagement with society.